The influence of listener experience, measurement scale and speech task on the reliability of auditory-perceptual evaluation of vocal quality - Jônatas do Nascimento Alves; Anna Alice Figueiredo de Almeida; Rosiane Yamasaki; Leonardo Wanderley Lopes (CoDAS, 2024)
ABSTRACT Purpose To assess the influence of the listener experience, measurement scales and the type of speech task on the auditory-perceptual evaluation of the overall severity (OS) of voice deviation and the predominant type of voice (rough, breathy or strain). Methods 22 listeners, divided into four groups participated in the study: speech-language pathologist specialized in voice (SLP-V), SLP non specialized in voice (SLP-NV), graduate students with auditory-perceptual analysis training (GS-T), and graduate students without auditory-perceptual analysis training (GS-U). The subjects rated the OS of voice deviation and the predominant type of voice of 44 voices by visual analog scale (VAS) and the numerical scale (score “G” from GRBAS), corresponding to six speech tasks such as sustained vowel /a/ and /ɛ/, sentences, number counting, running speech, and all five previous tasks together. Results Sentences obtained the best interrater reliability in each group, using both VAS and GRBAS. SLP-NV group demonstrated the best interrater reliability in OS judgment in different speech tasks using VAS or GRBAS. Sustained vowel (/a/ and /ɛ/) and running speech obtained the best interrater reliability among the groups of listeners in judging the predominant vocal quality. GS-T group got the best result of interrater reliability in judging the predominant vocal quality. Conclusion The time of experience in the auditory-perceptual judgment of the voice, the type of training to which they were submitted, and the type of speech task influence the reliability of the auditory-perceptual evaluation of vocal quality.